STRATEGI MEMBACA NYARING DI SEKOLAH DASAR - Widhiasih, Luh Ketut Sri; Dharmayanti, Putu Ayu Paramita (Institut Hindu Dharma Negeri Denpasar, 2017)
The low reading skills of students in Indonesia compared to the International encourages the government to issue a strategic policies that seek to build a love of the Indonesian people to read. At the level of the school, teachers as an executor of a policy use various strategies to improve reading comprehension of their students. One of the strategies used is reading aloud strategy. The implementation of reading aloud strategy in schools is often misunderstood, so it requires a clearer understanding of what it is reading aloud strategy and how its implementation. Reading aloud strategy is not just a way to teach reading but also a way to build a love of reading value. Love reading value character is important to get more attention in the middle of the decline ofÂ reading comprehension level of Indonesian students in the world level which can also affect the development of the country.